Electrophoretic Nanocrystalline Graphene Film Electrode for Lithium Ion Battery. Issue 1 (9th March 2015) - Kaprans, Kaspars; Bajars, Gunars; Kucinskis, Gints; Dorondo, Anna; Mateuss, Janis; Gabrusenoks, Jevgenijs; Kleperis, Janis; Lusis, Andrejs
Abstract: Graphene sheets were fabricated by electrophoretic deposition method from water suspension of graphene oxide followed by thermal reduction. The formation of nanocrystalline graphene sheets has been confirmed by scanning electron microscopy, X-ray diffraction and Raman spectroscopy. The electrochemical performance of graphene sheets as anode material for lithium ion batteries was evaluated by cycling voltammetry, galvanostatic charge-discharge cycling, and electrochemical impedance spectroscopy. Fabricated graphene sheets exhibited high discharge capacity of about 1120 mAh·g −1 and demonstrated good reversibility of lithium intercalation and deintercalation in graphene sheet film with capacity retention over 85 % after 50 cycles. Results show that nanocrystalline graphene sheets prepared by EPD demonstrated a high potential for application as anode material in lithium ion batteries.